2012
DOI: 10.14411/fp.2012.011
|View full text |Cite
|
Sign up to set email alerts
|

Two species of philometrid nematodes (Philometridae) from marine fishes off Japan, including Philometroides branchiostegi sp. n. from Branchiostegus japonicus (Malacanthidae)

Abstract: Nematodes of the family Philometridae Baylis et Daubney, 1926 include a large number of species parasitic in the body cavity and various body tissues of fishes (Moravec 2006). to date, 26 species of these parasites have been reported from marine and freshwater fishes in Japanese waters, including representatives of the genera Clavinema Yamaguti, 1935, Philometra costa, 1845 and Philometroides Yamaguti, 1935(ishii 1916a,b, 1931, Yamaguti 1935, 1941, 1961, Fujita 1940, Machida 1970, Moravec and Nagasawa 1989,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The body length is smaller than that of the gravid of P. carolinensis (Moravec et al, 2006) and larger than that of the gravid specimen of P. kiddakoi (Moravec et al, 2019) and gravid specimen of P. cryptocentri (Moravec et al, 2012). It is thinner when compared with the sub-gravid P. kiddakoi (Moravec et al, 2019), and the gravid specimen of P. cryptocentri (Moravec et al, 2012).…”
Section: Remarksmentioning
confidence: 98%
See 1 more Smart Citation
“…The body length is smaller than that of the gravid of P. carolinensis (Moravec et al, 2006) and larger than that of the gravid specimen of P. kiddakoi (Moravec et al, 2019) and gravid specimen of P. cryptocentri (Moravec et al, 2012). It is thinner when compared with the sub-gravid P. kiddakoi (Moravec et al, 2019), and the gravid specimen of P. cryptocentri (Moravec et al, 2012).…”
Section: Remarksmentioning
confidence: 98%
“…The present specimen is recovered from the gonad of host Lutjanus argentimaculatus (Forsskal, 1775) from Karachi coast, Pakistan. Other type species recorded are Philometra kidakoi (Moravec et al, 2019), from the ovary of Gymnothorax kidako (Temminck & Schlegel), reported in Japan; Philometra cryptocentri (Yamaguti, 1961) redescribed by Moravec et al (2012), from specimens recovered from the abdominal cavity of Acanthogobius flavimanus (Temminck & Schlegel), Pterogobius elapoides (Günther). Reported from the Southern Sea of Japan.…”
Section: Remarksmentioning
confidence: 99%
“…Knowledge of the fauna of philometrid nematodes (Philometridae) parasitising marine fishes in Japanese waters remains fragmentary. To date, a total of 20 nominal species of these parasites, belonging to the genera Clavinema Yamaguti, 1935 (1 species), Philometra Costa, 1845 (17 species) and Philometroides Yamaguti, 1935 (2 species), have been reported from marine representatives of the fish orders Perciformes, Pleuronectiformes, Scorpaeniformes, Siluriformes and Tetraodontiformes from off Japan (Ishii 1931, Yamaguti 1935, 1941, 1961, Machida 1970, Moravec and Nagasawa 1989, Moravec et al 1998, 2012a, 2018, Quiazon et al 2008a; see Nagasawa 2008 for the other literature).…”
mentioning
confidence: 99%
“…In the period from 1984-2009, samples of nematodes from Japanese fishes from Honshu, Shikoku and Hokkaido were collected by the Japanese co-author of the present study. A part of this material (nematodes from marine fishes) has already been evaluated in previous publications (Moravec et al 2010(Moravec et al , 2012a. Results of the morphological-taxonomical evaluation of nematodes recovered from Japanese inland fishes are presented here.…”
mentioning
confidence: 99%